Tourism Promotion Strategy Analysis: Increasing Destination Attractiveness in the Digital Era - Wulandari, Dwi Pratiwi (MSJ : Majority Science Journal, 2025)
This study aims to analyze effective tourism promotion strategies in increasing destination attractiveness in the digital era. Through the Systematic Literature Review (SLR) approach, this study examines various previous research results to identify the forms of promotion strategies commonly used, the effectiveness of digital media, and supporting and inhibiting factors for the success of digital tourism promotion. Data were collected from various scientific databases such as Google Scholar, Scopus, ScienceDirect, Emerald Insight, and Garuda, with inclusion criteria including Indonesian and English language articles published between 2015–2025 and relevant to the theme of digital tourism promotion. The article selection process followed the PRISMA flow, and the analysis was carried out using thematic analysis techniques. The results of the study showed that social media, official destination websites, and interactive digital campaigns were the dominant promotional strategies used. The effectiveness of digital promotion was greatly influenced by content quality, audience engagement, and communication consistency. In addition, it was found that technological support, human resource capacity, and collaboration between industry players and the government were key factors in the success of digital tourism promotion. This study provides strategic recommendations for destination managers to optimize the potential of digital media in attracting tourists and building a strong destination image.